Law and Medicine: the Influence of Fundamental Rights on the Corona-crisis and the Influence of the Corona-crisis on Fundamental Rights in the EU - Trstenjak, Verica (Medicine, Law & Society, 2021)
The article deals with the intersection of law and medicine, especially in the time of the Corona-crisis. It analyses restrictions of human/fundamental rights in the time of the Corona-crisis at the EU level. Conditions for restrictions of fundamental rights are provided by Article 52(1) of the EU Charter of Fundamental Rights. The case-law of the Court of Justice of the EU concerning the restrictions of fundamental rights in connection with health protection is also analysed. The last part provides an overview of some decisions of constitutional courts of EU Member States concerning the justifications of restrictions of fundamental rights during the Corona-crisis.